EFEKTIVITAS MEDIA ELEARNING MADRASAH TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN SEJARAH - Raudatul Jannah; Maria Ulfah; Ika Rahmatika Chalimi (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine the effectiveness of madrasah e-learning media on students' interest in learning history in class XI IPS 1 MAN 02 Pontianak. The method used is descriptive quantitative. The results of the study show that 1). effectiveness of madrasah e-learning media in history learning in class XI IPS 1 MAN 02 Pontianak, the results of respondents' answers with the majority of the percentage of 50% in the good category, 2). students' interest in learning using madrasah e-learning media in history learning in class XI IPS 1 MAN 02 Pontianak, the results of respondents' answers with the majority of the percentage of 85% in the sufficient category. 3). Regarding the effectiveness of madrasa e-learning media on students' interest in learning history in class XI IPS 1 MAN 02 Pontianak, it can be concluded of the regression test that the effect of the effectiveness of variable X on Y is 4.2%Keywords: Effectiveness, Madrasah E-learning, History Learning.